2021
DOI: 10.7861/clinmed.2020-0691
|View full text |Cite
|
Sign up to set email alerts
|

NHS England-funded CT fractional flow reserve in the era of the ISCHEMIA trial

Abstract: BackgroundThe National Institute for Health and Care Excellence (NICE) 2016 guidelines (CG95) recommend patients with new stable chest pain be investigated with computed tomography coronary angiography (CTCA). An updated guideline (MTG32) recommended using CT fractional flow reserve (CTFFR) as a gatekeeper to invasive coronary angiography (ICA) for patients with coronary stenosis on CTCA. Subsequently, NHS England negotiated a UK-wide contract with HeartFlow, the provider of CTFFR. We describe our experience w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Several studies have shown that CT-FFR is a useful method to recognize hemodynamicallysignificant CHD (12)(13)(14)(15)(16). Rasoul et al also suggested that CT-FFR could preliminarily screen patients for CAG (17)(18)(19). Other researchers also reported that CT-FFR improved the diagnostic performance of CTA (20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that CT-FFR is a useful method to recognize hemodynamicallysignificant CHD (12)(13)(14)(15)(16). Rasoul et al also suggested that CT-FFR could preliminarily screen patients for CAG (17)(18)(19). Other researchers also reported that CT-FFR improved the diagnostic performance of CTA (20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%